Relação entre ciúme romântico e satisfação conjugal - CARDOSO, Vanessa Alcântara (Universidade Federal do Pará, 2019)
In this study we aimed to measure the level of romantic jealousy of men and women who are in a loving relationship for at least 6 months, using the Scale of Romantic Jealousy - ECR as an instrument (Ramos , 2000). We also identified the perception of the satisfaction of the couple about their relationships according to Evolutionary Psychology, using the Questionnaire of Marriage and Relationship (MARQ) adapted by Russell and Wells (1993). We found that these variables have an important role in maintaining loving relationships by being major psychological mechanisms that evolved along the human phylogeny. The results showed that the degree of satisfaction of the sampled couples mainly fell into the “Satisfied Couples” and “Highly Satisfied” categories. We also found the five levels of romantic jealousy, the largest percentage concentrated in moderate level of jealousy. It was found that the variables are completely independent, refuting dropping claims that jealousy is bad for satisfaction in the relationship, and it contributes to the dissatisfaction of individuals in loving relationships. We can say only that it is one of the elements of the relationship necessary for the maintenance and custody of the partner, contributing to a union long enough to create offspring.